Numerical analysis of a masonry chimney supported by In-Situ assessment tools - Valter Lopes (2008)
At the end of the XIX and the beginning of the XX century there was a considerable industrial development in Portugal, characterized by the flourishing of several industrial plants. Brick masonry chimneys represent some of the most interesting examples of the industrial architectural heritage. The paper shows the case study of a chimney from a former ceramic factory near Porto city and that now is part of a cultural and leisure public park. With the main goal of evaluating the seismic vulnerability of existing structures, numerical models are often used without the proper knowledge of their mechanical characteristics. The focus on this paper is given on the construction of a realistic numerical model based on a detailed in-situ survey of the chimney, involving: geometrical characterization; visual inspection, with damage registration; structural/material assessment, based on in situ dynamic tests. Two different approaches regarding the chimney damage state were followed for the calibration of the numerical model. The models from both approaches were then subjected to accelerograms matching the chimney site conditions and the responses were compared, underlining the importance of a good mechanical characterization of the materials involved.